(untitled) (Innovate Conferences, 2025)
This lesson explores the linguistic and stylistic dimensions of zoonyms (animal names) in the English and Russian languages. It examines the lexical features, origins, word formation processes, and the stylistic functions of zoonyms, with a particular focus on diminutives, augmentatives, compounds, and derivatives. The lesson also delves into their metaphorical, symbolic uses, emotional connotations, and cognitive implications. The role of zoonyms in idiomatic expressions, proverbs, folk wisdom, literature, and cultural identity is highlighted, providing an in-depth view of how these words shape our perception of animals in different cultures. This lesson plan will engage students in a deep exploration of the linguistic, stylistic, and cultural dimensions of zoonyms, offering insights into the way animals shape human language, thought, and identity.